Experiences of non-formal education : a study of motivation sources and empowerment among facilitators - Lertkittisuk, Korrapin (2019)
The aim of the thesis is to gain more understanding of the motivation sources and empowerment outcomes of the participants who are facilitators in non-formal education. The conceptual framework includes concepts of motivation and empowerment. Altruism and egoism describe interconnection between motivation sources and concepts of motivation in parallel. To explain the empowerment outcomes, the specific concepts of empowerment are constructed by data-driven approach. The life story interview and participant observation are applied for data collection, and the thematic analysis is adopted as a tool to categorize and analyze the data. The interview data consists of eight facilitators from five organizations in three different countries: The United States, Finland, and Thailand.